2017
DOI: 10.4103/jhrs.jhrs_50_16
|View full text |Cite
|
Sign up to set email alerts
|

Does first serum beta-human chorionic gonadotropin value prognosticate the early pregnancy outcome in an In-vitro fertilisation cycle?

Abstract: Background:Pregnancies achieved through in-vitro fertilisation (IVF) are associated with adverse first trimester outcomes in comparison to spontaneously achieved pregnancies. In view of this, it is imperative to predict the success as well as prognosticate the pregnancy outcome of an IVF cycle not only for the clinicians but also the couples undergoing IVF. Serum beta-human chorionic gonadotropin (β-hCG) value has, thus, been used as a biomarker for pregnancy outcome after IVF and also an aid in counselling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In an in vitro fertilization-embryo transfer study [5], the prediction accuracy of HCG was better than that of progestin (P = 0.015). Monitoring of serum β-HCG [9] on the 15th day after the transfer of a cleavage stage embryo (3 days post in vitro fertilization) showed that when β-HCG was <500 mIU/ml, the rates of biochemical pregnancy, ectopic pregnancy, and missed abortion were all higher than when β-HCG was 501-1000 mIU/mL. The number of viable pregnancies was significantly reduced in the low β-HCG group.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro fertilization-embryo transfer study [5], the prediction accuracy of HCG was better than that of progestin (P = 0.015). Monitoring of serum β-HCG [9] on the 15th day after the transfer of a cleavage stage embryo (3 days post in vitro fertilization) showed that when β-HCG was <500 mIU/ml, the rates of biochemical pregnancy, ectopic pregnancy, and missed abortion were all higher than when β-HCG was 501-1000 mIU/mL. The number of viable pregnancies was significantly reduced in the low β-HCG group.…”
Section: Discussionmentioning
confidence: 99%
“…Because the date of conception with IVF is precise, a single measurement of serum β-hCG at 12 to 18 days following embryo transfer has been established as a reliable early indicator of pregnancy. [ 11 ] And biochemical pregnancy failure is usually defined as a serum β-hCG < 5 mIU/mL 14 days after embryo transfer without a visible gestational sac by TVS. [ 12 ] Here, we report a ruptured rectal ectopic pregnancy which was thought to a biochemical pregnancy failure at the first postoperative visit.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro fertilization-embryo transfer study [5], the prediction accuracy of HCG was better than that of progestin (P=0.015). Monitoring of serum β-HCG [9] on the 15th day after the transfer of a cleavage stage embryo (3 days post in vitro fertilization) showed that when β-HCG was <500 mIU/ml, the rates of biochemical pregnancy, ectopic pregnancy, and missed abortion were all higher than when β-HCG was 501-1000 mIU/mL. The number of viable pregnancies was signi cantly reduced in the low β-HCG group.…”
Section: Discussionmentioning
confidence: 99%